Local government finance in Ghana: Disbursement and Utilization of the MPs share of the District Assemblies Common Fund - Appiah-Agyekum, N. N.; Boachie-Danquah, N. Y.; Sakyi, E. K. (My University, 2013)
The establishment of the District Assembly Common Fund (DACF) in 1993 and concomitant percentage set aside for Members of Parliament (MPs) in 2004 aims to support local governments and legislators in pro-poor development activities in their communities and constituencies. In spite of the importance of the MPs’ share of the District Assemblies Common Fund (MPsCF) in financing local level development in Ghana, very little is known about monitoring systems and procedures on the disbursement and utilization of the funds. The study therefore assessed qualitative data derived from interviews with officials from selected Local Government Authorities (LGAs) as well as other key stakeholders in the disbursement and utilization of the fund. The study findings point to the absence of legislative instrument on the management of the MPsCF. Further, monitoring of the fund was a responsibility shared by the LGAs and other external stakeholders. Finally, the effectiveness of monitoring the disbursement and utilization of the MPsCF was strongly influenced by the relationship between the Chief Executive of the Local Government Authority (LGCE) and MPs in the local government area.